The Role of Smart Automation in Tourism Industry Management using Smart PLS - Oscar Jayanagara; Sri Watini (International Transactions on Artificial Intelligence, 2023)
The main objective of this research is to critically examine existing research and the application of smart automation (Smart PLS) in the tourism industry. Additionally, this study proposes a new evaluation framework to identify vulnerabilities in the adoption of smart automation. This is a synthesis and evaluation study, where qualitative findings about the implementation of smart automation in the tourism industry are presented. The study uses a seven-dimensional evaluation framework based on Rogers' diffusion theory (2003) to assess the current implementation of intelligent automation. The vulnerability of adopting smart automation in the tourism industry depends largely on the type of smart automation used. Search/booking engines, virtual agents, and chatbots are three types of intelligent automation that have high vulnerability levels. The limitations and implications of this study are that it bridges the foundations of innovation diffusion theory and the application of smart automation. The findings from this research can help researchers, developers, and managers evaluate the vulnerability of adopting smart automation technology in the tourism industry. This paper is also one of the few papers that assess the vulnerability of adopting smart automation in the tourism industry, and it develops a theory-based evaluation framework to systematically evaluate smart automation innovation in the tourism industry.